Compressive strength of mortar containing ferronickel slag as replacement of natural sand - Saha, Ashish; Sarker, Prabir (Elsevier BV, 2017)
Uses of various industrial by-products have been extensively studied in the past few decades in order to enhance the sustainability of construction industry. By-products can be used as alternatives to binders as well as aggregates in concrete. A large quantity of granulated ferronickel slag (FNS) is produced as a by-product in the smelting of nickel ore. This paper presents the effects of using ferronickel slag as a replacement of natural sand in cement mortar. The slag was produced by sea water-cooling of the by-product from the smelting of garnierite nickel ore. The grain size distribution of the slag was found suitable for using as fine aggregate in concrete. It was found that flow of fresh mortar increased with the increase of FNS up to 50% replacement of sand and then declined with further increase of FNS. The compressive strength of the hardened mortar specimens increased with the increase of FNS up to 50% and then declined with further increase of FNS. Use of fly ash as 30% cement replacement together with FNS as replacement of sand increased the flow of fresh mortar and decreased the strength of hardened specimens.